A tradeoff between fitness‐related traits mask facilitation in a semiarid ecosystem. Issue 8 (8th May 2020) - Molina‐Montenegro, Marco A.; Baldelomar, Mariela; Atala, Cristian; Torres‐Díaz, Cristian
Abstract : In stressful environments, a nurse plant can ameliorate harsh biotic and abiotic conditions for another plant species that grows within its canopy. This canopy can act as a barrier for herbivores, reducing damage to the protected plants inside, but it can also reduce access to pollinators possibly resulting in a tradeoff between survival and reproductive output. In a semi‐arid ecosystem, the shrub Porlieria chilensis acts as a nurse, increasing soil moisture, nutrients and reducing temperature inside its canopy compared to open areas. Flourensia thurifera is one of the beneficiary shrubs that can grow inside P. chilensis, where it shows increased survival and performance compared to open areas. However, growing inside P. chilensis ' canopy may reduce pollinator visit. We aim to evaluate the possible tradeoff between survival and reproduction in F. thurifera individuals growing inside and outside the canopy of P. chilensis . This was achieved through a field experiment were we measured survival, pollinator visits and seed output of F. thurifera plants growing inside and outside the canopy of P. chilensis . Flourensia thurifera individuals had a higher survival when growing within the canopy of P. chilensis and had lower pollinator visits and seed output compared to plants growing in open areas. Thus, we found a significant negative correlation between plant survival and seed output considering both conditions (inside or outside nurses), evidencing a tradeoff between these traits. The tradeoff evidenced here could have large impact at the population and community level. On one hand, this tradeoff could mask possible nurse effects in other species, since they could show a similar net fitness in both microhabitat (inside or outside nurses). Finally, we propose a theoretical model to assess the change in the shape of this tradeoff under future climatic conditions where temperature and precipitation are predicted to vary due to climate change.